Dietary restriction and gonadal signaling differentially regulate post‐development quality control functions in Caenorhabditis elegans - Shpigel, Nufar (John Wiley and Sons Inc., 2019)

(untitled) (Aging Cell)
Protein homeostasis is remodeled early in Caenorhabditis elegans adulthood, resulting in a sharp decline in folding capacity and reduced ability to cope with chronic and acute stress. Endocrine signals from the reproductive system can ameliorate this proteostatic collapse and reshape the quality control network. Given that environmental conditions, such as food availability, impact reproductive success, we asked whether conditions of dietary restriction (DR) can also reverse the decline in quality control function at the transition to adulthood, and if so, whether gonadal signaling and dietary signaling remodel the quality control network in a similar or different manner. For this, we employed the eat‐2 genetic model and bacterial deprivation protocol. We found that animals under DR maintained heat shock response activation and high protein folding capacity during adulthood. However, while gonadal signaling required DAF‐16, DR‐associated rescue of quality control functions required the antagonistic transcription factor, PQM‐1. Bioinformatic analyses supported a role for DAF‐16 in acute stress responses and a role for PQM‐1 in cellular maintenance and chronic stress. Comparing the stress activation and folding capacities of dietary‐ and gonadal‐signaling mutant animals confirmed this prediction and demonstrated that each differentially impacts cellular quality control capabilities. These data suggest that the functional mode of cellular quality control networks can be differentially remodeled, affecting an organism's ability to respond to acute and chronic stresses during adulthood.